[Bewitched, bothered and bewildered ; All in the mind ; Lihim ng panahon - Lazaro, Cheche (The Probe Team, 1990)
Tackles interviews with Dr. Jimmy Tan patients cured by "albularyo" and "manggagamot" about "kulam" and bad spirits ; mental dimension healing, pranic healing and prayer ; and interviews with Madame Auring, Aling Joleng, Rogelio Cruz who claimed to be faith healer ; and had direct communication with God.